2016
DOI: 10.1016/j.foodchem.2015.10.139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment on antioxidant capacity and (poly)phenolic compounds of selected vegetables

Abstract: 22The impact of cooking heat treatments (frying in olive oil, frying in sunflower oil and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
99
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 33 publications
17
99
3
1
Order By: Relevance
“…The increase in antioxidant capacity and the number of peaks present in the free phenolic DDS‐RB sample (Figure b) compared to free phenolic NS‐RB sample (Figure a) is most likely due to the heating process used during stabilization treatments. Similar findings were also reported elsewhere (Juániz et al, ; Xu, Ye, Chen, & Liu, ; Yılmaz & Gökmen, ). In the study by Xu et al (), an increase in citrus peel‐derived free phenolic compounds was observed after heat treatment.…”
Section: Resultssupporting
confidence: 91%
“…The increase in antioxidant capacity and the number of peaks present in the free phenolic DDS‐RB sample (Figure b) compared to free phenolic NS‐RB sample (Figure a) is most likely due to the heating process used during stabilization treatments. Similar findings were also reported elsewhere (Juániz et al, ; Xu, Ye, Chen, & Liu, ; Yılmaz & Gökmen, ). In the study by Xu et al (), an increase in citrus peel‐derived free phenolic compounds was observed after heat treatment.…”
Section: Resultssupporting
confidence: 91%
“…The impact of common domestic and technological treatments on lavonoid composition in onions was studied [23,[91][92][93][109][110][111]. During technological and culinary treatments, important chemical and biochemical reactions occur in onion tissue.…”
Section: Cooking: Frying Microwaving Baking and Boilingmentioning
confidence: 99%
“…It takes place because of a complicated form of sunroot tubers. Under modern production conditions there is a necessity to create the resource-saving equipment, correspondent to the world requirements [10]. Today the one of most prospective directions of sunroot cleaning quality improvement and decrease of raw material losses is a creation of such equipment, which working principle is based on the combined effect of thermal and mechanical processes on a product [11].…”
Section: Introductionmentioning
confidence: 99%